Opportunity-Reduction Supervision Strategies With Domestic and Family Violence Probationers and Parolees - Schaefer, Lacey; Williams, Gemma C.; Moir, Emily (Frontiers in Psychology, 2022)
Many forms of supervision strategies traditionally utilized by probation and parole officers emphasize service brokerage, case management, and compliance. Conversely, there is a growing evidence-base that demonstrates how community corrections practices can be (and have been) improved through supervision frameworks of behavior change oriented around criminogenic needs. Toward this end, recent advances in penology have applied the tenets of environmental criminology theories to community corrections practices, seeking to identify and modify each individual’s opportunity-based risks for reoffending. In this article, using data from an Australian experimental trial, we explore the utility of an “Environmental Corrections” approach to the supervision of domestic and family violence perpetrators serving probation and parole orders, an offending cohort with growing political and public pressures. Quantitative analyzes indicate that this opportunity-reduction supervision framework was effective in reducing recidivism among all offenders. Amongst probationers and parolees on community corrections orders for domestic and family violence offenses only, rates of reoffending were 15.41% lower for offenders at the treatment site compared to the control site, although this difference was not statistically significant. A thematic analysis of semi-structured interviews with these clients highlights that through the Environmental Corrections trial, they learned strategies for identifying, avoiding, and resisting opportunities to reoffend. Combined, this evidence suggests that opportunity-reduction supervision tactics may hold promise for limiting recidivism amongst domestic and family violence perpetrators, although further research is required.